Association between daily TV time and physical fitness in 6- to 14-year-old Austrian youth - Greier, Klaus (Transl Pediatr, 2019)
BACKGROUND: Physical activity (PA) and sedentary behaviors have been associated with various health outcomes in youth, including overweight/obesity and physical fitness. Limited information, however, is available on the independent association between TV time and physical fitness in children and adolescents. METHODS: A total of 3,293 (55.1% male) youth between 6 and 14 years of age were randomly selected from 29 Austrian schools. Body weight and height were measured according to standard procedures and BMI percentiles were determined based on German reference values. Physical fitness was assessed with the German Motor test (DMT6-18), which evaluates cardiorespiratory endurance, muscular strength, power, strength endurance, agility, speed and flexibility. Information on daily TV time and participation in club sports was obtained via standardized questionnaires. RESULTS: Participants were 9.8±2.3 years of age and almost half of them (48.5%) reported a TV time >2 hours/d. TV time increased significantly with age. High TV consumption was associated with significantly lower physical fitness and these results remained after adjusting for body weight. Youth exceeding current TV time recommendations had a 60% higher risk of having poor or very poor fitness compared to those with a TV time <2 hours/day. CONCLUSIONS: High TV time is associated with poor physical fitness in youth. Accordingly, intervention strategies need to target a meaningful utilization of TV and other screen-based activities in addition to the promotion of PA in order to ensure sufficient physical fitness in youth.